Extensive reading with adult learners of English as a second language: habits and attitudes of a group of Malaysian pre-university students - Engku Ibrahim, Engku Haliza; Othman, Khairiah (2008)
Many language instructors acknowledge the important role extensive reading plays in the acquisition of a second language. There are many ways in which an extensive reading programme can be intergrated into a language curriculum. This study reports of feedback from 2,461 learners of English as a second language in a pre-university programme where extensive reading has been integrated as part of the language curriculum. Feedback was also obtained from 38 teachers involved in the extensive reading programme. Among others, this research reports on learners’ attitudes towards reading in general and also reading in the target language. Their responses will be compared to the response from the teachers